Analysis of ophthalmic emergencies - (:unkn) unknown (CUKUROVA UNIV, FAC MEDICINE, 2016)
Purpose: The aim of this study was to determine the admission complaints, demographic characteristics, etiology, diagnosis, and outcome of patients who admitted to emergency department with eye-related complaints. Material and Methods: All patients, over the age of 18, who admitted to emergency department with eye-related complaints between June 2011 and May 2012, were included prospectively in this study. Demographic characteristics, etiology, admission complaints, diagnosis, and outcome of the patients in the emergency department were evaluated with statistical analysis. Results: At the time of the study, a total of 201427 adult patients admitted to our emergency department and 3256 (1.6%) were included in the study. 77.5% of the patients (2524) were males. The most frequent diagnosis was trauma (30.3%) in female gender, whereas it was superficial foreign bodies (46.2%) in male gender. The most common cause of trauma was home accidents (57.4%) in females, whereas it was work accidents (73%) in males. Of patients admitted due to vision loss (0.46%), it was identified that these patients were older and visual loss is more dependent on non-traumatic ophthalmic emergencies. Conclusions: The majority of cases of ophthalmic emergencies are work accidents in young active workingmen patients group. The most common complaints of patients are trauma and superficial foreign bodies. Vision loss depends mostly on non-traumatic ophthalmic emergencies seen in the elderly.
Keywords: Emergency; eye; vision loss; OCULAR RELATED EMERGENCIES; EYE INJURIES; TRAUMA; POPULATION; EPIDEMIOLOGY; CASUALTY